Intramolecular Cycloaddition of Imines of Cysteine Derivatives - Cabral, Ana M. T. D. P. V. (1998)
Azomethine ylides were generated from Schiffs bases of S-allylcysteine methyl ester and their intramolecular 1,3-dipolar cycloadditions were studied. These reactions led to the synthesis of thieno[3,4-b]pyrrole derivatives in good yield